PENGARUH INFORMATIVENESS, ENTERTAINMENT, DAN IRRITATING TERHADAP ATTITUDE TOWARD SOCIAL MEDIA ADVERTISING PADA MASYARAKAT KOTA MATARAM - Yeldy Dwi Genadi; Lalu M. Furkan (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
This research was done to the citizen of Mataram City Province of West Nusa Tenggara and aimed to analyze the influencing of attitude toward social media advertising that is informativeness, entertainment, and irritation. This research hypothesis was anticipated by a independent variable influencing by significantly to attitude toward social media advertising. This research use the appliance of data taken (instrument) in the form of questionaire laying open about informativeness, entertainment, and irritation. So that data taken by good hence questionaire have to be up to standard of validity and reliability. Analysis technique used at this research was multiple linier regression analysis to know the accurate independent variable influencing toward dependent variable. As for multiple linier regression model have to be up to standard of public assumption of regression by conducting classical assumption test. Pursuant to result of multiple linier regression analysis proven by that independent variable in the form of informativeness (X1), entertainment (X2), and irritation (X3) have the influence which significant to dependent variable by that is attitude toward social media advertising. While based on result the t test proven by that independent variable by partially have an effect on by significant to dependent variable, so that hypothesis at this research was fully supported. Independent variable which is dominant influencing to the attitude toward social media advertising is entertainment.Keywords :Social Media Advertising, Informativeness, Entertainment, Irritation, Attitude.